Optical Butyrometric reading tube: An Approach towards Gerber Automation - Desai, Pankti; Pandya, Utpal (Indian Journal of Dairy Science, 2022)
The Gerber Test is among the oldest and most widely used laboratory test with significant applications that include determination of Fat of different dairy products. A major limitation of reference Gerber test is handling of its complex test equipment Butyrometer and its manual reading procedure. To make the device auto readable detail understanding of   butyrometer design and its operation is required. In this research paper, the design of newly developed butyrometer reading tube and measurement reading with it is discussed. The developed butyrometer reading tube can provide real time sample analysis after centrifugation and is compatible to several commercial Butyrometers. The prototype Butyrometer system demonstrate monitoring of fat for four different type of milk sample contains different fat range. The collected data are valuable for analytical purposes (e.g., quality control, milk price estimation), or as feedback to the user. The system adds new functionality to existing manual Gerber test, saving users time and providing useful feedback. This concept enables new analytical applications for an instrument that has remained largely unchanged for decades. Successful application of the equipment would be very helpful to all types of Dairy vendors.